MOTIVASI INDONESIA BEKERJASAMA DENGAN MALAYSIA DALAM BIDANG INFRASTRUKTUR (STUDI KASUS: MELAKA-PEKANBARU POWER INTERCONNECTION 2002-2017) - Hompi, Hamri; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aims to explain the motivation of Indonesia making a framework cooperation with Malaysia in the form of IMT-GT. In the year of 2002, Malaysia and Indonesia have agreed to build electric cable which spread out from Pekanbaru (Indonesia) to Melaka (Malaysia) . This Projeck is called â€œMelaka-Pekanbaru Power Interconnectionâ€. Through this cooperation could fulfill the electrical energy needs in both countries, especially in Melaka and Pekanbaru. This research is guided by qualitative explanation methods. All of datas in this research are based on books, internet, media, journals, and other references. This researc has been built by international cooperation theory by K.J. Holsti. This theory said that cooperation is made by merger of uniformity from national, regional, and global issues which need more attention from more than one state. The result of this research shows that Indonesia making a framework cooperation with Malaysia in the form of Melaka-Pekanbaru Power Interconnection is to fulfill the electrical energy needs, especially in Pekanbaru. This cooperation which has been built since 2002 is planned to be done it the year of 2017. Keywoards: Power interconnection, Indonesia Malaysia Thailand growth triangle, motivation